An Experimental and Numerical Study of Axially Loaded Lightweight Concrete Wall Panels - Ting, Timothy Zhi Hong (Curtin University, 2019)
This research investigates the axial behaviour of lightweight concrete wall through experimental and numerical studies, and leads to the development of two equations which can predict wall axial capacity with better accuracy. These equations can consider the effect of concrete elastic modulus and are incorporated with factors to allow for slenderness ratio, eccentricity and compressive strength non-linearity. The versatility of the equations is proven through comparison with the results from experiments, numerical simulations and published literatures.